Respuestas
Respuesta dada por:
3
Racionalizando:
==============
![=\sqrt[3]{\frac{x}{y}} \\ \\ = \frac{ \sqrt[3]{x} }{ \sqrt[3]{y} } \:\:\:\:\:\:\:\:\:\:\: Multiplicamos\: por \: \sqrt[3]{ y^{2}}\\ \\ =\frac{ (\sqrt[3]{x} )( \sqrt[3]{ y^{2} }) }{ (\sqrt[3]{y})( \sqrt[3]{ y^{2} }) } \\ \\ = \frac{ \sqrt[3]{x y^{2} } }{ \sqrt[3]{ y^{3} } } \:\:\:\:\:\:\:Simplificando\:raiz\:3\: y\: exponente \:3\\ \\ = \frac{ \sqrt[3]{x y^{2} } }{y} =\sqrt[3]{\frac{x}{y}} \\ \\ = \frac{ \sqrt[3]{x} }{ \sqrt[3]{y} } \:\:\:\:\:\:\:\:\:\:\: Multiplicamos\: por \: \sqrt[3]{ y^{2}}\\ \\ =\frac{ (\sqrt[3]{x} )( \sqrt[3]{ y^{2} }) }{ (\sqrt[3]{y})( \sqrt[3]{ y^{2} }) } \\ \\ = \frac{ \sqrt[3]{x y^{2} } }{ \sqrt[3]{ y^{3} } } \:\:\:\:\:\:\:Simplificando\:raiz\:3\: y\: exponente \:3\\ \\ = \frac{ \sqrt[3]{x y^{2} } }{y}](https://tex.z-dn.net/?f=%3D%5Csqrt%5B3%5D%7B%5Cfrac%7Bx%7D%7By%7D%7D++%5C%5C++%5C%5C+%3D++%5Cfrac%7B+%5Csqrt%5B3%5D%7Bx%7D+%7D%7B+%5Csqrt%5B3%5D%7By%7D+%7D++%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A+Multiplicamos%5C%3A+por+%5C%3A+%5Csqrt%5B3%5D%7B+y%5E%7B2%7D%7D%5C%5C++%5C%5C+%3D%5Cfrac%7B+%28%5Csqrt%5B3%5D%7Bx%7D+%29%28+%5Csqrt%5B3%5D%7B+y%5E%7B2%7D+%7D%29+%7D%7B+%28%5Csqrt%5B3%5D%7By%7D%29%28+%5Csqrt%5B3%5D%7B+y%5E%7B2%7D+%7D%29+%7D++%5C%5C++%5C%5C+%3D+%5Cfrac%7B+%5Csqrt%5B3%5D%7Bx+y%5E%7B2%7D+%7D+%7D%7B+%5Csqrt%5B3%5D%7B+y%5E%7B3%7D+%7D+%7D++%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3ASimplificando%5C%3Araiz%5C%3A3%5C%3A+y%5C%3A+exponente+%5C%3A3%5C%5C++%5C%5C+%3D++%5Cfrac%7B+%5Csqrt%5B3%5D%7Bx+y%5E%7B2%7D+%7D+%7D%7By%7D+)
==============
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años